CHARACTERISTICS OF THE GROWING SEASON FROM THE PERSPECTIVE OF RISKS OF CROP PRODUCTION IN THE SOUTHERN TAIGA OF WESTERN SIBERIA (Proceedings of the YSU C: Geological and Geographical Sciences, 2025)
In recent decades, there has been an increase in the number of dangerous phenomena in the southern taiga of Western Siberia, with the greatest increase occurring during the growing season. Late spring and early autumn frosts, heavy and prolonged precipitation, low humidity, and high wind activity have a significant negative impact on crop production in the region under study. The paper presents the result of a decadal analysis of a complex of dangerous and adverse events, which allowed us to assess the temporal dynamics and identify the features of the spring–summer, summer and autumn seasons of the growing season.
Keywords: Southern taiga of Western Siberia; dangerous and unfavorable phenomena; crop production; risks; vegetation period